1993
DOI: 10.1002/j.1552-4604.1993.tb03949.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Pharmacologic Effects of OPC‐21268, a Nonpeptide Orally Active Vasopressin V1 Receptor Antagonist, in Humans

Abstract: The pharmacokinetics, safety, and pharmacologic effects of OPC-21268, a nonpeptide orally active vasopressin V1 receptor antagonist, have been investigated in 33 healthy subjects. First, 24 subjects were randomly divided into 3 groups of 8, 6 of whom were given 2 ascending single oral doses out of 6 (10, 50, 150, 300, 450, and 600 mg) of OPC-21268 after an overnight fast. The remaining two subjects in each group received placebo as control at each dosing. Additionally, after this procedure, the 6 subjects who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…An animal study with labeled "4C-OFLX clearly demonstrated greater accumulations in excretory organs such as the salivary gland and the trachea, in comparison with those in the serum (17). From 0.5 to 24 h after the single oral dose, the drug distribution to these organs was two to four times higher than that to the serum, and these higher distributions were maintained after multiple (once a day for 21 days) doses (16). These results suggested that OFLX may be particularly well distributed to the excretory organs and may be secreted into the extravascular fluids, by a process(es) which probably involves not only passive but also active transport.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…An animal study with labeled "4C-OFLX clearly demonstrated greater accumulations in excretory organs such as the salivary gland and the trachea, in comparison with those in the serum (17). From 0.5 to 24 h after the single oral dose, the drug distribution to these organs was two to four times higher than that to the serum, and these higher distributions were maintained after multiple (once a day for 21 days) doses (16). These results suggested that OFLX may be particularly well distributed to the excretory organs and may be secreted into the extravascular fluids, by a process(es) which probably involves not only passive but also active transport.…”
Section: Resultsmentioning
confidence: 97%
“…Ofloxacin concentrations in serum, sputum, and saliva were fitted to a pharmacokinetic model by a nonlinear least-squares method, with the microcomputer program MULTI (22). We used an open one-compartment model with first-order absorption, and the weight for each analysis was 1 (16 …”
mentioning
confidence: 99%
“…Japan), weighing 180-200 g. were housed in individual metabolic cages, fed on a standard rat powder chow(20g/day: Oriental Yeast Co.. Japan) in a deep cup with negligi ble spillage and given water ad libitum. They received two doses of Adriamycin (2 mg/kg) via tail vein at an interval of 3 weeks [1], At week 3 just after the second Adriamycin injection, the rats were ran domly divided into four groups, and the standard rat chow was sup plied with the drugs as follows: group 1, control rats without drugs (n = 6); group 2, rats given V 1 receptor antagonist (OPC-21268 [14][15][16], 200 mg/kg/day; n = 5): group 3. rats given V2 receptor antagonist (OPC-31260 [17.18], 50 mg/kg/day; n = 5). and group 4. rats given both V 1 and V2 antagonists (200 and 50 mg/kg/day, respectively; n = 5).…”
Section: Experimental Designmentioning
confidence: 99%
“…Nonetheless, many investigators have modified the structure (11)(12)(13)(14), but have as yet found no nonpeptide V1 / V2 receptor antagonist. Our previous reports (15,16), however, described a nonpeptide, orally active VI receptor antagonist, OPC-21268, and then OPC-31260, a nonpeptide V2 receptor antagonist, also has been developed. In vitro animal experiments using [3H ]AVP have demonstrated that OPC-31260 is a selective V2 receptor antagonist, and this agent has been shown to behave as an aquaretic agent in rats (9).…”
Section: Discussionmentioning
confidence: 99%